A life cycle assessment of an enterprise's low-carbon emissions model: The Xinjiang Shihezi pig farm faecal treatment biogas project as a case study. (15th February 2022) - Wang, Xiaowan; Dong, Xiaobin; Wang, Xue-Chao; Zhang, Peng; Liu, Ranran; Klemeš, Jiří Jaromír; Zheng, Jianghua
Abstract: The requirement of carbon emission reduction promotes the continuous implementation and development of low carbon emission mode in typical high-carbon industry aquaculture, especially in the resourceful treatment of terminal waste. However, the previous studies usually focus on a single process or chain, the difference between the long-chain (LC) and automated integration (AI) in the overall environmental impact needs to be quantified and standardised. This paper intends to make a comparative study on two waste treatment biogas projects of aquaculture, a typical industry with high resource consumption and pollution emission in industry and agriculture, and a typical production mode case of aquaculture. The life cycle assessment method is adopted to analyse the environmental impact intensity, identify key link materials, and put forward targeted improvement and optimization schemes. The study found the LC system's comprehensive environmental impact (CEI) is smaller, which is 59.73% less than the AI system. Biogas slurry returning to the field can effectively avoid inorganic fertilizer input. The pretreatment and storage of feces are the key stages. The key substances are NH3 and nitrogen oxides. Suggestions were put forward to optimize the manure management process. In practical pig farms, the process of dry-cleaning manure pre-treatment, automatic fermentation gas production and final biogas slurry filtration drip irrigation should be promoted. Graphical abstract: Image 1 Highlights: Enterprise low-carbon emission model on agriculture waste management is explored. Long-chain and automated integration models have been involved and compared. The long-chain model has much less, 59.73%, environmental impact than the automated integration model. The pre-treatment and storage of feces are the key stages in the waste management china.